PEMBUATAN SENSOR PROXIMITY BERBASIS SENSOR INDUKTIF METODE DIFFRENSIAL BERBENTUK KOIL DATAR - Yulkifli, Yulkifli (IAIN Batusangkar, 2012)
The physical principle of flat coil sensor was based on the changing inductivity of a flat coil due to disturbance of conductive material in its electromagnetic fields, so that eddy current on the conductive material was occurred. The displacement between flat coil and conductive material was a function of the total inductance L of the sensor system, which will be measured as resonance frequency by using an inductive capacitive oscillator. The measurement system consists of a flat coil, oscillator circuit LC, multimeter and micrometer. In measuring, as independent variables were distance of object and time, while dependent variable was output voltage of flat coil sensor by using differential technique. Data was collected through two ways i.e. direct and indirect measurement. Then data was analyzed by using graph methods and error analysis. Data analysis shown that: 1). The output sensor without differential technique isn?t linear with distance of conductive material; 2). The output sensor with differential technique is inversely proportional with distance of conductive material with negative sensitivity 1,2783 Volt/mm ; 3). The precision of sensor was high with average of precision is 0,999, and 4). The stability of sensor was also high with small output voltage variation. Key words: sensor, flat coil, characteristics, sensitivity, precision, stability